Identification of Two Nuclear Import Signals in the α-Gene Product ICP22 of Herpes Simplex Virus 1 - Stelz, Gerhard; Rücker, Elke; Rosorius, Olaf; Meyer, Gerold; Stauber, Roland H.; Spatz, Martin; Eibl, Martha M.; Hauber, Joachim (Virology (New York, N.Y.), 2002)
The herpes simplex virus 1 (HSV-1) infected cell protein 22 (ICP22) is a multifunctional viral regulator that localizes in the nucleus of infected cells. ICP22 is required for optimal virus replication in certain cell types and is subject to extensive posttranslational modification. To map the signals in ICP22 which mediate its efficient nuclear localization, we investigated the nuclear import of fusion proteins comprising various fragments of ICP22 fused to green fluorescent protein (GFP) or β-galactosidase (β-Gal). These data demonstrated that ICP22 contains two independent regions with nuclear localization signal (NLS) activity. NLS1 maps to ICP22 amino acid position 16–31 and closely resembles the classical bipartite NLS of the type originally identified in nucleoplasmin. In contrast, NLS2 maps to ICP22 amino acid position 118–131 and contains multiple critical basic residues. Furthermore, fusion of both NLSs to chimeric glutathione-S-transferase (GST)–GFP protein and subsequent cytoplasmic microinjection of the respective transport substrates allowed us to monitor nuclear import in real-time. These data demonstrated that both ICP22-derived NLSs mediated efficient nuclear import with identical kinetics, resulting in complete nuclear accumulation of the chimeric transport cargoes at approximately 30 min postinjection. Finally, our data provide new insights into the domain structure of the multifunctional α-gene product ICP22 of HSV-1.